Prenatal Diagnosis of 45,X/46,XX Mosaicism with Presence of SRY Gene. A Case Report - Pedro Alí Díaz-Véliz Jiménez; María Antonia Ocaña Gil; Leydi María Sosa Águila; Belkis Vidal Hernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
The most common karyotype of the Turner syndrome is 45,X, although it may occur as mosaic 45,X/46,XX. In the Provincial Medical Genetics Center, a 42-year-old pregnant woman underwent an amniocentesis which led to the detection of mosaic Turner Syndrome (45,X/46,XX). A male was diagnosed through ultrasound and a sample of amniotic fluid was sent to the National Medical Genetics Center to confirm it. A study of the SRY gene was completed and the result was positive. The patient decided to terminate the pregnancy. The pathology report showed a fetal corpse of 25, 3 weeks of gestation, with penis and morphologically normal scrotal sacs, presenting alterations by cysts and hypoplasia of the prostate and seminal vesicles as well as testicular absence. In the literature, cases of XX males are considered uncommon while those combining a mosaic 45, X/46, XX with a SRY gene are less addressed; and therein lies the importance of this case. This article presents the results of a prenatal diagnosis of this rare chromosomal aberration.